2014
DOI: 10.1186/1752-1947-8-251
|View full text |Cite
|
Sign up to set email alerts
|

Delayed primary closure of contaminated abdominal wall defects with non-crosslinked porcine acellular dermal matrix compared with conventional staged repair: a retrospective study

Abstract: IntroductionSynthetic mesh has been used traditionally to repair abdominal wall defects, but its use is limited in the case of bacterial contamination. New biological materials are now being used successfully for delayed primary closure of contaminated abdominal wall defects. The costs of biological materials may prevent surgeons from using them. We compared the conventional staged repair of contaminated abdominal wall defects with a single-stage procedure using a non-crosslinked porcine acellular dermal matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…7 Mechanical property of PP mesh provides the strength of abdominal wall fascia to prevent abdominal retraction. However, PP mesh may cause acute and chronic inflammation, fistula formation, and chronic abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Mechanical property of PP mesh provides the strength of abdominal wall fascia to prevent abdominal retraction. However, PP mesh may cause acute and chronic inflammation, fistula formation, and chronic abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene (PP) is one of the most commonly used non-degradable synthetic mesh materials for abdominal wall defects and hernia repair. 7 Mechanical property of PP mesh provides the strength of abdominal wall fascia to prevent abdominal retraction. However, PP mesh may cause acute and chronic inflammation, fistula formation, and chronic abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion was based on the poor host tissue incorporation shown by Strattice though adhesion formation was scarce. However, a recent retrospective clinical study [1] has shown that Strattice could be a suitable alternative to conventional staged repair. Among the benefits cited by the authors were faster patient recovery, early restoration of abdominal wall function and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of properties boasted by bioprostheses has led to their rapidly expanding use, especially in settings of contamination or low-grade infection [1,2]. As a basic characteristic, these prosthetic materials slowly become degraded in the host until their complete elimination [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to previous laparotomies, the abdominal wall fascia could not be approximated without tension and fascial edges still could not reach one another during closure [7] . Moreover, due to the contamination of the abdomen with secretions, it was not possible to insert a synthetic mesh for abdominal closure based on the high risk of infection (it is important to note that biological mesh is also very expensive and not routinely available to surgeons in lower socioeconomic nations) [8] , [9] . To address this issue, this new abdominal wall defect (which was more limited than the first one) was covered by ipsilateral skin flaps as a novel procedure (please refer to Fig.…”
Section: Case Presentationmentioning
confidence: 99%